Molecular insights into paediatric breast fibroepithelial tumours. Issue 5 (22nd August 2018) - Tay, Timothy K Y; Guan, Peiyong; Loke, Benjamin N; Nasir, Nur Diana M; Rajasegaran, Vikneswari; Thike, Aye Aye; Lian, Derrick; Chang, Kenneth T E; Teh, Bin Tean; Ng, Cedric C Y; Tan, Puay‐Hoon
Abstract : Aims: This study aims to examine the molecular genetics of paediatric breast fibroepithelial tumours through the targeted sequencing of 50 genes. Methods and results: Formalin‐fixed paraffin‐embedded tissues of fibroepithelial tumours diagnosed in a cohort of patients aged 18 years and below were subjected to next generation sequencing using the Haloplex Target Enrichment System. Twenty‐five conventional and 17 juvenile fibroadenomas were studied, with MED12 mutations found in 53.8 and 35% of the tumours, respectively. There was also one benign fibroepithelial neoplasm with hybrid features of juvenile papillomatosis and infarcted benign phyllodes tumour‐like areas. Most tumours did not have mutations in well‐known cancer driver genes, none harboured TERT promoter mutations, while 25.6% (11 of 43) showed no mutations. Metachronous and synchronous tumours were found to have mutational heterogeneity with some containing mutations in MED12 ; other genes or no mutations were detected at all. Four of eight giant fibroadenomas (size 5 cm or larger) had no mutations detected, suggesting that there are other molecular mechanisms driving their growth. Tumours with MED12 mutations incidentally had a significantly higher stromal mitotic count compared with those without. Conclusion: While paediatric fibroepithelial lesions can have cellular stroma potentially raising concern for phyllodes tumour, their lack of TERT promoter and cancer driver mutations is reassuring. The absence of mutations in a significant proportion of tumours, especially the giant fibroadenomas, warrants investigation of pathogenetic mechanisms beyond those involving the 50 genes.